2023
DOI: 10.1039/d3nr03231k
|View full text |Cite
|
Sign up to set email alerts
|

Nanogels designed for cell-free nucleic acid sequestration

Yuhang Huang,
Shangyu Li,
Logan W. C. Zettle
et al.

Abstract: Chronic wounds exhibit over-expression of cell-free deoxyribonucleic acid (cfDNA), leading to a prolonged inflammation and non-healing wounds. Scavenging excessive cfDNA molecules is a promising strategy for chronic wound treatment. Nanoparticles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…30 These data suggest that the use of surface positively charged nanoparticles as nanocarriers enabled electrostatically driven nanoparticle scavenging, thereby improving drug accumulation inside the cells and thus optimum therapeutic efficacy. 31 Effects of Surface Chemical Moieties on Nanoparticle Release. Exocytosis rates determine the residency time of nanoparticles in the cell, which, in turn, determines the toxicity profile of nanoparticles to cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 These data suggest that the use of surface positively charged nanoparticles as nanocarriers enabled electrostatically driven nanoparticle scavenging, thereby improving drug accumulation inside the cells and thus optimum therapeutic efficacy. 31 Effects of Surface Chemical Moieties on Nanoparticle Release. Exocytosis rates determine the residency time of nanoparticles in the cell, which, in turn, determines the toxicity profile of nanoparticles to cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A study also reported that amino-functionalized polymeric nanoparticles could retain intracellularly for up to 8 days without altering the physiological functions of the cell . These data suggest that the use of surface positively charged nanoparticles as nanocarriers enabled electrostatically driven nanoparticle scavenging, thereby improving drug accumulation inside the cells and thus optimum therapeutic efficacy …”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharide particles can be formed by physical or chemical crosslinking of PS molecules. Physical crosslinking can be achieved via hydrogen bonding, [94] ionic crosslinking, [95] hydrophobic interactions, [96] or host-guest interactions. [97] Figure 4, top row, shows images of exemplary PSPs and specifies [94] Copyright 2018, ACS.…”
Section: Particle Formation By Physical Crosslinking Of Polysaccharid...mentioning
confidence: 99%
“…Reproduced with permission. [95] Copyright 2023, RSC. (c) Alginate particles formed due to hydrophobic interactions.…”
Section: Particle Formation By Physical Crosslinking Of Polysaccharid...mentioning
confidence: 99%
See 1 more Smart Citation